THE RELEVANCE OF QUR'ANIC ECOTHEOLOGY TO ḤIFẒ AL-BĪ'AH FROM A TAFSIR MAQĀṢIDĪ PERSPECTIVE - Ahmad Torik; Abdul Halim (Yayasan Dinamika Literasi Jambi, 2026)
This study examines the relationship between ecotheology in the Qur’an and the concept of ḥifẓ al-bī’ah (environmental preservation) through a maqāṣidī exegetical approach. Amid the global ecological crisis, which is largely driven by human behavior, the maqāṣidī approach to Qur’anic interpretation becomes particularly significant, as it goes beyond a purely textual analysis of Qur’anic verses to explore the broader objectives of Islamic law (maqāṣid al-sharī‘ah). This research employs a qualitative method based on library research, utilizing thematic analysis of selected Qur’anic verses, including Q. 7:56 (Al-A‘rāf), Q. 2:205 (Al-Baqarah), Q. 11:61 (Hūd), and Q. 30:41 (Al-Rūm). The findings indicate that Islamic ecotheology has a strong relevance to the maqāṣid al-sharī‘ah, positioning environmental preservation as an integral component of the primary objectives of Islamic law. Accordingly, maqāṣidī exegesis can serve as a constructive and solution-oriented approach for fostering ecological awareness among Muslims.